Visible Light Communications: Challenges and potential - O'Brien, D (2011)
Visible Light Communications uses modern solid-state lighting sources for free-space communication, and can also provide other functions such as illumination and information display. This paper outlines some the challenges, and potential of this technique. © 2011 IEEE.